2019
DOI: 10.1080/09638288.2019.1697763
|View full text |Cite
|
Sign up to set email alerts
|

Growing up with a rare genetic disease: an interpretative phenomenological analysis of living with Holt-Oram syndrome

Abstract: c EA 7364-RADEME-Maladies RAres du D eveloppement et du M etabolisme: du ph enotype au g enotype et a la Fonction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Existing knowledge about children with RD describes the psychosocial experiences of their families and caregivers [ 16 , 17 ] yet the child with RD must remain the focal point. Children with RD are more likely to encounter significant challenges in their functioning at home, at school, and in their community [ 18 ]. However, there is scant research characterizing the child’s own experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Existing knowledge about children with RD describes the psychosocial experiences of their families and caregivers [ 16 , 17 ] yet the child with RD must remain the focal point. Children with RD are more likely to encounter significant challenges in their functioning at home, at school, and in their community [ 18 ]. However, there is scant research characterizing the child’s own experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Growing up with a rare genetic disease is associated with patients’ experiences of feeling different and fearing rejection. [ 28 ] The experiences of patients with dystonia also showed that they experienced psychosocial fears caused by the stigma of the disease and, in other words, rejection. [ 29 ] In the present study, all participants had experiences of disapproval or discrimination in their community and being strange in people's eyes.…”
Section: Discussionmentioning
confidence: 99%